2020
DOI: 10.9734/arrb/2019/v34i630169
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom Production Benefits, Status, Challenges and Opportunities in Bangladesh: A Review

Abstract: Compacted information on mushroom cultivation in relation to production, performance, problems and prospects is very important for developing this sector. So, the aim of the review paper is to compile information on mushroom cultivation in Bangladesh. Mushroom production is increasing due to high demand of domestic market and export potentiality. In Bangladesh 40000 MT mushrooms are produced during 2018-19. Oyster, Reishi, Milky, Button, Straw and Shiitake mushrooms are most preferable species and cultivated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Although consumption of mushrooms around the globe has a long history, cultivation and consumption of mushrooms are very recent in Bangladesh [16], since people are still largely unaware of the nutritional and medicinal importance of this food item. Though mushroom cultivation was introduced in late 1980's by Bangladesh Agricultural Research Council (BARC), vigorous training by National Mushroom Extension and Development Centre (NMED C) of Bangladesh has made it more popular in recent days with the yearly national production increasing from 10,500 metric tons in 2009-2010 to 40,000 metric tons in 2018-2019 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although consumption of mushrooms around the globe has a long history, cultivation and consumption of mushrooms are very recent in Bangladesh [16], since people are still largely unaware of the nutritional and medicinal importance of this food item. Though mushroom cultivation was introduced in late 1980's by Bangladesh Agricultural Research Council (BARC), vigorous training by National Mushroom Extension and Development Centre (NMED C) of Bangladesh has made it more popular in recent days with the yearly national production increasing from 10,500 metric tons in 2009-2010 to 40,000 metric tons in 2018-2019 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In 1960, scientists investigated the basic active principles of mushrooms that are health-promoting effects [36]. Different scientific modern pharmacological literature has confirmed that [34] the medicinal properties of mushrooms include anti-oxidant, anti-inflammatory, anti-carcinogenic, anti-microbial, antibacterial, anti-fungal, anti-diabetic, anti-angiogenic, immune modulatory, hepatoprotective, hypoglycemic [33], anti-viral, anti-tumor, anti-hypercholesterolemic, anti-hypertensive, protecting the liver, promoting general fitness [11], anti-asthmatic, anti-obesity, anti-atherosclerotic, and anti-ulcer, besides being used as functional foods. e medicinal and pharmacological importance of P. ostreatus is illustrated in Figure 2 and Table 2.…”
Section: Medicinal Importance and Health-promoting Effectsmentioning
confidence: 98%
“…Worldwide, Pleurotus ostreatus is one of the most common types of cultivated mushrooms [8], and next to the Agaricus bisporus mushroom it is the 2nd largest commercially produced mushroom globally, especially in Europe, Africa [9,10], and Asian countries (especially India, South Korea, China, Taiwan, Japan, ailand, and Vietnam) which are the main producers and consumers of P. ostreatus mushrooms with approximately 99% of the total volume [9]. It was first cultivated in the USA in 1900 [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Peppers are also well known for its high content in bioactive compounds and strong antioxidant properties including neutral phenolic compounds or flavonoids called quercetin, luteolin, and capsaicinoids [4]. The nutritional status of Bangladeshi people is a matter of great concern as more than half of the populations have been suffering from malnutrition [5], [6]. So, consumption of sweet pepper can relieve the suffering from malnutrition of Bangladeshi people to some extent, because they provide more vitamin, minerals, protein, and strong antioxidant @ @ @ @ @ @ properties.…”
Section: Introductionmentioning
confidence: 99%